Dual-effect of Holmium(III) oxide and Boron Carbide reinforcement on physical, microstructural evolution and gamma-ray shielding performance of 316L-SS - Yayla, Nihal; Albayrak, M. Gokhan; Guler, Omer; Almisned, Ghada; Sen Baykal, Duygu; Alkarrani, Hessa; Tekin, Huseyin Ozan (Sage Publications Inc, 2025)
This study provides one of the first comprehensive evaluations of 316L stainless steel composites reinforced with 10 wt.% B4C and varying concentrations of Ho2O3, proposing a new compositional design for simultaneous structural enhancement and dual gamma-neutron shielding optimization. XRD analysis confirmed the predominance of the austenitic phase with minor martensitic peaks at higher Ho2O3 levels. SEM and EDX results revealed uniform dispersion and improved densification with increasing oxide content. The 316L-B4C-20%Ho2O3 composite exhibited the highest mass attenuation coefficient (0.8953 cm(2)/g) and linear attenuation coefficient (6.73 cm(-1)) at 0.1 MeV, demonstrating superior gamma-ray shielding capability. The effective electron density increased from 2.86 x 10(23) to 5.82 x 10(23) electrons/cm(3), while the energy absorption buildup factor (EABF) showed a consistent decrease with higher oxide concentrations. Although a slight reduction in fast neutron removal cross-section was observed, the composite maintained satisfactory neutron attenuation performance. Overall, the findings indicate that the 316L-B4C-20%Ho2O3 system offers a promising balance between structural stability and dual radiation protection, making it a strong candidate for next-generation nuclear shielding materials.
Keywords: 316L stainless steel; Ho2O3 reinforcement; gamma-ray shielding; structural properties; energy absorption buildup factor